2012
DOI: 10.1891/0198-8794.32.3
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 1<BR> Resilience in Adulthood and Later Life: What Does it Mean and Where Are We Heading?

Abstract: These chapters refl ect the fact that resilience is best understood as not only multidimensional in nature, but also in a complementary fashion, that resilience as a meaningful construct is also domain specifi c. In these respects, Smith and Hayslip discuss the construct of resilience: its evolution and development, the historical context in which an emphasis on resilience has surfaced, and issues related to the defi nition and measurement of resilience in the context of protective factors, risk, and adversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 33 publications
2
56
0
1
Order By: Relevance
“…Several studies have found that LGBT older adults are strengthened through “crisis competence,” applying lessons learned from being a sexual minority to the aging process (Friend, 1991, p. 110). The biopsychosocial model for late life resilience (Smith & Hayslip, 2012) suggests that older adults can engage individual, interpersonal, and environmental resources to combat elements of risk and adversity. Professionals in the field need the knowledge, skills, and values to identify intrapersonal and interpersonal resources with older LGBT consumers, and to assist them in addressing their needs, those of their families, and other support systems.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have found that LGBT older adults are strengthened through “crisis competence,” applying lessons learned from being a sexual minority to the aging process (Friend, 1991, p. 110). The biopsychosocial model for late life resilience (Smith & Hayslip, 2012) suggests that older adults can engage individual, interpersonal, and environmental resources to combat elements of risk and adversity. Professionals in the field need the knowledge, skills, and values to identify intrapersonal and interpersonal resources with older LGBT consumers, and to assist them in addressing their needs, those of their families, and other support systems.…”
Section: Methodsmentioning
confidence: 99%
“…Older adults frequently experience concentrated non-normative and age-related changes such as declines in health and functioning, decreased mobility, diagnosis of chronic or terminal illness, death of spouse and/or friend, loss of social status, decreased financial security, retirement, changes in residence, and social ageism (Aldwin & Igarashi, 2012; Smith & Hayslip, 2012). These adversities range from daily challenges to catastrophic experiences that directly impact one’s ability to age successfully and impact the entire family system.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a strengths perspective reflects the identification of the family's strengths, that is, survival skills, and knowledge, resources, and skills that will enhance family functioning (Early, 2001). Although empowerment and such constructs as self-efficacy (Bandura, 1977), resilience (Rutter, 2007), or resourcefulness (e.g., Zauszniewski & Musil, 2013) are not interchangeable, these ideas may be precursors or outcomes associated with empowerment, consistent with a view that various characteristics or processes are protective regarding susceptibility to negative outcomes in individuals (Smith & Hayslip, 2012). This article explores the measurement of empowerment in a sample of grandparent caregivers, for whom being empowered is most important to their mental and physical health as well as to their ability not only to parent a grandchild but also to access needed services crucial to their own well-being as well as that of the grandchildren they are raising.…”
Section: Introductionmentioning
confidence: 91%